(Janko Kos in) problem narodnih identifikacij - Potocco, Marcello (Primerjalna književnost, 2011)
The essay argues for a definition of nation that takes into consideration both the constructed nature of national identities as well as their relative stability and continuity. Combined with Ricoeur's idea of narrative identity, literature is defined as a possible agent of national self-representation, mainly when a nation is constructed on basis of common symbolic heritage instead of on the principal of jus soli.
Keywords: Kos, Janko, 1931-; slovenska literarna veda; književnost; literature; narod; people; družba; society; nacionalna identiteta; kulturna identiteta; nacionalna književnost